Studies on Mastitis in the camel: Cytological, bacteriological and diagnostic aspects. - Abdurahman, O.A. Sh (Swedish University of Agricultural Sciences, 1996)
The camel supports the survival of millions of people in arid and semi-arid areas of the world. Information on mastitis screening tests and their relevance for application in the camel are lacking. The present work was carried out to study the occurrence and causes of mastitis in camels. The aim was also to assess the value of inflammatory markers i.e. California Mastitis Test (CMT), somatic cell count (SCC), the level of adenosine triphosphate (ATP), N-acetyl-B-D-glucosaminidase activity (NAGase) and Serum Albumin (SA) as indicators of subclinical mastitis in the camel. Quarter milk samples (n = 391) from 101 camels in the Sudan were examined. Milk from 170 (43.5%) yielded pathogenic bacteria. Str. agalactiae, other Str. spp., Staph. aureus, coagulase-negative staphylococci (CNS), and E. coli were isolated from milk. Thirty-two (8.2%) quarter milk samples yielded mixed cultures, and 189 (48.3%) yielded no growth. Mean values for CMT, SCC, ATP and NAGase were significantly higher for quarters infected with major pathogens compared to those infected with minor pathogens and non-infected quarters. Serum albumin content in milk was not affected by infection status of the quarter. The ability of SCC, CMT and ATP to predict a positive bacteriology increased slightly when two or three tests were combined. Staph. aureus and CNS were recovered from 36 (22.5%) of 160 milk samples from 7 bactrian camels. Infected quarters had significantly higher mean values for SCC and CMT than non-infected quarters. These values were significantly influenced by the stage of lactation. Both SCC and CMT were found valuable in predicting infection status of the udder. The fine structure of leukocytes from the udders of lactating and non-lactating bactrian camels and from blood were studied. The morphological study of milk sediments revealed the presence of numerous (63% to 99%) cell fragments ranging in diameter from 1.5-27.5 $μ$m. The cell fragments were bounded by a plasma membrane, had no nuclei and contained mitochondria and abundant rough endoplasmic reticulum. Among leukocytes, macrophages were the dominant cells (60%) recovered from milk and udder secretions during the dry period, followed by lymphocytes (31%) and neutrophils (9%). Flow cytometry and fluorescent microscopy was used to study cell populations in blood and milk and their phagocytic activities. Three clusters of blood cells (mononuclear cells, neutrophils and eosinophils) were identified. In milk, leukocytes and particles scattered widely all over the fluorogram, with no distinct cluster formation. Cellular fragments were found to take a relatively higher stain of green fluorescence. The mean percent phagocytosis of PMNL cells isolated from blood was $71.8± 5.9%$ at 10 min and increased to $97.3\ ±\ 0.5%$ at 60 min. The average number of bacteria per phagocyte was $8.7± 2.1$ and $13.1± 0.9$ at 10 and 60 minutes incubation time respectively. The oxidative burst activity of phagocytic cells isolated from camel blood and mammary gland was studied using a chemiluminescence (Cl) assay. The PMNL isolated from camel blood mounted a luminol-dependent Cl response upon stimulation with opsonized zymosan or S. aureus. The leukocytes isolated from the mammary gland gave similar Cl responses to those of blood PMNL but to a lower magnitude. The Cl responses induced by blood and mammary gland leukocytes were associated with degranulation and the release of lysosomal enzymes such as myeloperoxidase (MPO).